Necesidad de incluir en el código de trabajo y Ley Orgánica de Servicio Público, un artículo que disponga la obligatoriedad de presentar como único documento habilitante, el certificado de nacimiento, para beneficiarse con la licencia por paternidad - Encalada Rivera, Marcos Eduardo (2015)
In this context we find to the license for parenthood, like one of the rights constitutionally guaranteed in our country, reason for which all the citizens, who have had enormous pleasure and responsibility in being parents must take refuge in this right that guarantees the father, be close to its familiar nucleus in a stage of vital importance and of unrepeatable opportunity, as it is the birth of a son or a daughter. The present investigation analyzes the labor law of the license for parenthood, the origins of this permission are established inside the Ecuadoran legislation. The analysis of statistical data that appears is fundamental because it allows posicionar to the Ecuador opposite to nearby countries and the states of the European continent; finally there propose reforms to themselves to the laws that govern at present the license for parenthood, based on the professionals' criteria of the offices of human talent those who argue that if rules do not exist as for the demand of the document to be demanded to obtain the above mentioned right